2021
DOI: 10.1213/ane.0000000000005503
|View full text |Cite
|
Sign up to set email alerts
|

Leftover Opioid Analgesics and Disposal Following Ambulatory Pediatric Surgeries in the Context of a Restrictive Opioid-Prescribing Policy

Abstract: BACKGROUND: Opioid analgesics are commonly prescribed for postoperative analgesia following pediatric surgery and often result in leftover opioid analgesics in the home. To reduce the volume of leftover opioids and overall community opioid burden, the State of Tennessee enacted a policy to reduce initial opioid prescribing to a 3-day supply for most acute pain incidents. We aimed to evaluate the extent of leftover opioid analgesics following pediatric ambulatory surgeries in the context of a state-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…A systematic review by Sheth et al 20 found that overprescription of opioids was common after sports medicine procedures, with more than one-third of prescribed opioids remaining after utilization after surgery. Similar to the results of our study, Stone et al 21 described opioid utilization patterns after pediatric ambulatory surgery and reported over 90% of individuals having leftover opioids, with only 42% reporting disposal of these medications. The aforementioned studies all provide similar results to this study, demonstrating that patients undergoing orthopaedic surgery vastly underutilize their prescribed opioids based on typical prescribing patterns, which opens up the potential for community retention and illicit diversion.…”
Section: Discussionsupporting
confidence: 90%
“…A systematic review by Sheth et al 20 found that overprescription of opioids was common after sports medicine procedures, with more than one-third of prescribed opioids remaining after utilization after surgery. Similar to the results of our study, Stone et al 21 described opioid utilization patterns after pediatric ambulatory surgery and reported over 90% of individuals having leftover opioids, with only 42% reporting disposal of these medications. The aforementioned studies all provide similar results to this study, demonstrating that patients undergoing orthopaedic surgery vastly underutilize their prescribed opioids based on typical prescribing patterns, which opens up the potential for community retention and illicit diversion.…”
Section: Discussionsupporting
confidence: 90%
“…However, state‐level PMP's were not associated with reduction in opioid misuse and opioid use disorder in a study of adults taking part in the National Survey of Drug use and Health 17 . Other studies have found that restricting of opioid prescribing to children and adolescents, have been much less successful in reducing leftover opioids 16,18,19 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies suggest that opioid prescribing patterns after pediatric surgeries indicate that there are more opioids provided than what is needed for appropriate recovery 24–26 . Stone et al found that restricting postsurgical opioids to a 3‐day supply, still resulted in the vast majority of opioids going unused with >50% of parents retaining leftover opioids for future use 19 . There is an urgent need for research aimed at matching postsurgical opioid prescription with actual patient demand, in order to reduce the prevalence of leftover medication.…”
Section: Discussionmentioning
confidence: 99%
“…Yet recommendations from an expert surgical panel, also published in 2021, list pediatric adenotonsillectomy as a procedure in which “opioid‐free postoperative analgesia may be possible for some patients under some circumstances.” 3 Practical applications of national guidelines through The National Tonsil Surgery Registry in Sweden showed that half the departments surveyed prescribed rescue medications, including opioids, while the other half did not 25 . Literature has shown that children often receive more opioid doses than are needed to treat postoperative pain and that these left‐over medications are routinely left undisposed of with the potential for misuse and diversion 28–32 . However, the risk of over‐prescribing medications must be carefully balanced by the risks of the undertreatment of post‐tonsillectomy pain which include poor oral intake, dehydration, and prolonged recovery time 33 .…”
Section: Discussionmentioning
confidence: 99%